Exploring the role of Transcranial magnetic stimulation in cognitive impairment and sarcopenia: a narrative review - Wang, Yuhong; Li, Weichao; Dong, Tingting; Xu, Rui; Ai, Qing; Yang, Lili; Gai, Xuesong; Li, Li (Frontiers in Human Neuroscience, 2025)
Sarcopenia and cognitive impairment (CI) are major contributors to disability among the elderly, diminishing their quality of life and placing also a significant burden on healthcare systems and societies. There are currently no effective treatments for sarcopenia and CI. Interestingly, recent research has revealed a strong connection between these two conditions. Although the exact mechanisms of this relationship remain unclear, factors such as chronic inflammation, mitochondrial oxidative stress, and impaired communication through the muscle-brain axis have been put forward. Transcranial magnetic stimulation (TMS) is a non-invasive brain stimulation technique that can modulate neural plasticity and reduce inflammation and oxidative stress, demonstrating considerable potential for improving CI and motor function disorders. In this review, we summarize the relationship between sarcopenia and CI and discuss their shared mechanisms of action. In addition, we aim to provide new research insights and treatment directions by describing the physiopathological mechanisms modulated by TMS and its therapeutic potential for treating CI and sarcopenia.